Surgical causes of abdominal pain in children: a retrospective study - Dhanaram, Balaji; Chandrasekar, Sakthivel; Muthukumaraswamy, Baskar (International Surgery Journal, 2018)
Background: Abdominal pain is a very prevalent problem in children and one of the common causes for visit to the hospital. They may be of acute or chronic presentation and depending on severity may also require admission to hospital. Methods: This is a retrospective study conducted in our hospital over a period of 3 years. About 200 children who came to the hospital with abdominal pain and received treatment in surgical outpatient or referred to surgery department from emergency were included in this study and all relevant data were collected. Results: The pain was found to be more in boys and in the age group of 9 to 12years. The most common cause was found to be mesenteric adenitis followed by acute appendicitis. About 38% of children required surgical intervention on that admission due to various surgical causes. Conclusions: The database of our retrospective study regarding age and sex incidence, clinicopathological features and therapeutic outcome was comparable to other studies in various literatures.